2007
DOI: 10.1111/j.1945-5100.2007.tb00590.x
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive imaging and Raman spectroscopy of carbonate globules from Martian meteorite ALH 84001 and a terrestrial analogue from Svalbard

Abstract: Abstract-We report a comprehensive imaging study including confocal microRaman spectroscopy, scanning electron microscopy (SEM), and 3-D extended focal imaging light microscopy of carbonate globules throughout a depth profile of the Martian meteorite Allan Hills (ALH) 84001 and similar objects in mantle peridotite xenoliths from the Bockfjorden volcanic complex (BVC), Svalbard. Carbonate and iron oxide zoning in ALH 84001 is similar to that seen in BVC globules. Hematite appears to be present in all ALH 84001 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
119
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(124 citation statements)
references
References 50 publications
5
119
0
Order By: Relevance
“…One hypothesis contends that the ALH 84001 carbonates have a number of characteristics that indicate their low temperature (< ∼100 • C) deposition in a dynamic environment during perhaps several different episodes (Corrigan and Harvey 2004;Halevy et al 2011;Holland et al 2005;McSween and Harvey 1998;Niles et al 2005Valley et al 1997;Warren 1998). Another hypothesis suggests that the carbonates formed in a rapidly cooling environment which was initially at higher temperature (>150°C) and cooled to ∼30°C (Eiler et al 2002;Leshin et al 1998;Romanek et al 1994;Steele et al 2007), although this is now directly disputed by recently reported clumped isotope results (Halevy et al 2011).…”
Section: Formation Environments and Insight Into Martian Climate Historymentioning
confidence: 99%
See 1 more Smart Citation
“…One hypothesis contends that the ALH 84001 carbonates have a number of characteristics that indicate their low temperature (< ∼100 • C) deposition in a dynamic environment during perhaps several different episodes (Corrigan and Harvey 2004;Halevy et al 2011;Holland et al 2005;McSween and Harvey 1998;Niles et al 2005Valley et al 1997;Warren 1998). Another hypothesis suggests that the carbonates formed in a rapidly cooling environment which was initially at higher temperature (>150°C) and cooled to ∼30°C (Eiler et al 2002;Leshin et al 1998;Romanek et al 1994;Steele et al 2007), although this is now directly disputed by recently reported clumped isotope results (Halevy et al 2011).…”
Section: Formation Environments and Insight Into Martian Climate Historymentioning
confidence: 99%
“…Hydrothermal alteration of basaltic crust could produce CH 4 and sequester CO 2 in carbonates: the low intrinsic oxygen fugacity (fO 2 ) of martian basalt may force oxidized carbon supplied by magmatic degassing or crustal carbonates to reduce to CH 4 during water-rock interaction (Lyons et al 2005). Steele et al (2007) argued that the carbonates in ALH 84001 formed under similar high temperature, low fO 2 conditions resulting in the simultaneous formation of carbonates and macromolecular carbon.…”
Section: Hydrothermal Environmentsmentioning
confidence: 99%
“…A previous study investigating the gases in a bubble inside a fulgurite reports finding carbon dioxide and carbon monoxide, the origin of these gases were attributed to the plant matter at the point of a lightning strike (Navarro-Gonzalez et al 2007). Similarly, Steele et al (2006) have reported that they identified polyaromatic compounds from a glassy region of the Shergottite, Nakhite, Chassignite Martian meteorite Alan Hills 84001 and from a volcanic basalt specimen from the Svalbard Arctic Mars analogue site.…”
Section: Resultsmentioning
confidence: 99%
“…Clearly, the presence of polyaromatics, albeit unidentified on a molecular basis, in a meteorite and a volcanic glass (Steele et al 2006) lends credence to the assertion that PAHs could also have survived the thermal shock of a terrestrial lightning strike. This is the first observation, as far as we can ascertain, of the nondestructive detection, identification and location of organic material incorporated into the matrix of a fulgurite.…”
Section: Resultsmentioning
confidence: 99%
“…A similar analysis of PAHs in the Allan Hills (ALH) Martian meteorite 84001 uncovered PAHs localized in and around carbonate globules (15,16). This was perhaps the most controversial observation made using L 2 MS, because interpretation of how these PAHs were generated is a matter of continuing debate and has stimulated a significant amount of work (17,18). PAHs were not detected in ALH84001 fusion crust, nor were they found to be depth-dependent, as would be expected for terrestrial contaminants.…”
Section: Review Of L 2 Ms For the Study Of Extraterrestrial Materialsmentioning
confidence: 99%